22 Distribution of high sensitivity troponin taken without conventional clinical indications in critical care patients and its association with critical care mortality. (17th July 2020) - Hinton, Jonathan; Augustine, Maclyn; Gabara, Lavinia; Mariathas, Mark; Allan, Rick; Borca, Florina; Nicholas, Zoe; Beecham, Ryan; Gillett, Neil; Kwok, Shing; Cook, Paul; Grocott, Michael; et al.
Abstract : Background: High sensitivity troponin (hs-cTn) concentrations above the manufacturer's upper limit of normal (ULN) are frequently seen outside the context of MI, particularly in critical care patients. The potential value of hs-cTn as a biomarker for prognosis in CC patients has never before been systematically explored. Aims: 1. To describe both the distribution of hs-cTn in critical care and 2. the association of this distribution with clinical outcomes, including in hospital mortality. Methods: Consecutive patients admitted to the three adult CC units (cardiothoracic (CCCU), general (GCCU), neuroscience (NCCU)) over a six month period had hs-cTnI tests performed serially throughout the admission, regardless of whether the supervising team had identified a clinical indication. Except when requested for clinical reasons, the results were nested and not revealed to patients or clinicians. The association between hs-cTnI concentration and clinical outcome was evaluated. Results: After excluding patients diagnosed with a type 1 MI, there were 1, 563 patients remaining in the study cohort (CCCU 530, GCCU 750, NCCU 283). The median hs-cTnI was 77ng/L (IQR 11-1932ng/L), with 1081 (69.2%) patients above the manufacturer-provided ULN. Overall there was a bimodal distribution; GCCU and NCCU were positively skewed and CCCU negatively skewed (figure 1 ). Concentrations above the ULN were associated with increasing age, comorbidity, markers of illness severity and need for organ support (table 1 ). On multivariate analysis the degree by which the admission hs-cTnI concentration was above the ULN remained an independent predictor of critical care mortality (figure 2 ), but not length of stay for patients in NCCU and GCCU. Furthermore, the addition of the degree by which the hs-cTnI concentration was above the ULN to the Acute Physiology and Chronic Health Evaluation (APACHE) II score improved the area under the curve for critical care mortality (from 0.828 to 0.846 (p<0.001)). Peak hs-cTnI concentration and the degree of hs-cTnI change did not provide additional prognostic information compared with the admission hs-cTnI alone. Conclusion: Admission hs-cTnI concentration, taken regardless of a clinical indication, is an independent predictor of ICU mortality and provides additional discriminative ability to the APACHE II score alone. This assay may represent a novel prognostic biomarker on admission in critical care settings. Conflict of Interest: Unrestricted research grant from Beckman Coulter (who had no role in the study design, data collection, analysis or interpretation).